The importance of activating the reform of direct and indirect respiratory function problems in the context of dental orthodontic treatment - AlShishakli, Mahmoud; Massoud, Naji; Alshuraiki, Khaldoun; Jabban , Mohammmad Osama; Kasem, Issam; Jalali, Sinan Al; Alnohaily, Majeda (Jour Med Resh and Health Sci, 2021)
In this paper and from the point of view of the need to move towards for the adoption of alternative and more attractive solutions in the context of dental orthodontic treatment adopts the beginning of four-dimensional diagnosis and treatment that takes into account the functions associated and in a way that restores them to what they were programmed to get the highest aesthetic and vital results and the most stable and stable, the problems of respiratory function were studied and discussed in the context of dental orthodontic treatment: First: with its direct and related effects adjacent to the teeth and jaws through the model of the appearance of a disability in the nasal respiratory tract somehow leads to a defect in that dynamic balance of the so-called dental field, which may result, for example, narrowing in the upper tooth arch with overlay and protrusion of teeth as a result of excessive pressure from the outcome of external forces and other results and on the two tooth arcs, which brings to our attention here the need to activate the reform of the function Direct respiratory to restore that dynamic balance Second: its indirect effects on the different structures of the teeth, jaws and face and their growth and diseases associated with that function, which reach them in terms of being part of the general physical condition that is affected by the effectiveness of the entire respiratory function, as in the case of hypoxia This draws our attention here to the need to activate respiratory function reform with its auxiliary and indirect effects and especially by stimulating stem cells to promote healing towards more aesthetic and vital results. And through the method of treatment in gas pressure chambers that tries to resemble a return to the normal lifestyle in terms of respiratory function, and thus helps patients who are difficult to return. As for those who have the ability, it is recommended for them to return to the normal lifestyle in terms of respiratory function, in addition to various breathing exercises based on the above scoring on the purposes.